2007
DOI: 10.1109/tnsm.2007.030105
|View full text |Cite
|
Sign up to set email alerts
|

Traffic Engineering an Operational Network with the TOTEM Toolbox

Abstract: Abstract-We explain how the TOTEM toolbox can be used to engineer an operational network. TOTEM is an open source TOolbox for Traffic Engineering Methods which covers IPbased and MPLS-based intradomain traffic engineering (TE) algorithms, but also interdomain TE. In this paper, we use the toolbox as an off-line simulator to optimise the traffic of an operational network. To help an operator to choose between an IP-based or MPLS-based solution, or to find the best way to loadbalance a network for a given traffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In order to evaluate the performance of AMPLE, we use the real topologies and traffic traces from the GEANT and Abilene networks that are provided by the TOTEM Project [10]. We present results based on a 7-day long traffic traces dataset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the performance of AMPLE, we use the real topologies and traffic traces from the GEANT and Abilene networks that are provided by the TOTEM Project [10]. We present results based on a 7-day long traffic traces dataset.…”
Section: Resultsmentioning
confidence: 99%
“…We present results based on a 7-day long traffic traces dataset. Although the dataset in [10] provides traffic traces measured every 5 minutes, for consistency with the GEANT scenario, we also use 7-day long traffic matrices at the interval of every 15 minutes. In this article we compare the following optimization methods:…”
Section: Resultsmentioning
confidence: 99%
“…The traffic matrices have been derived every 15 minutes for several months. We present results based on a 7-day long traffic matrices dataset obtained from the TOTEM Project [17]. The Abilene network topology contains 12 nodes and 30 links, most of which are OC192, but the link between Indianapolis and Atlanta has 2.5Gbps capacity.…”
Section: Experiments Setupmentioning
confidence: 99%
“…We use the TOTEM toolbox [17] to compute a set of link weights for multiple traffic matrices. The objective is to make the IGP TE robust to traffic demand uncertainty.…”
Section: Multi-tmmentioning
confidence: 99%
“…We also analyzed the recommendations from routers vendors such as [10], [11], [12], [13] as well as configuration problems found by tools such as rcc [7], minerals [6] and others [5], [14], [15], [16]. Based on this survey, we found that most of the objectives, and in particular the low-level ones, could be expressed by using three main different patterns : presence (and non-presence), uniqueness and symmetry.…”
Section: A Patterns Of Configuration Objectivesmentioning
confidence: 99%